Diesel engine performance, emissions and combustion characteristics of castor oil blends using pyrolysis. (December 2020) - Attai, Youssef A.; Abu-Elyazeed, Osayed S.; ElBeshbeshy, Mohamed R.; Ramadan, Mohamed A.; Gad, Mohamed S.
Castor biodiesel (CBD) was manufactured by slow pyrolysis of oil from highly yielded seeds with anhydrous sodium hydroxide catalyst. An experimental study of engine's performance, emissions and combustion characteristics using biodiesel blended with gas oil in volumetric ratios of 0, 10, 25, 50, 75, and 100% at different loads was performed. Increase of CBD percentage in the blend led to a reduction in engine's thermal efficiency, cylinder pressure, net heat release rate, and smoke emission. The exhaust gas temperature, specific fuel consumption, unburned hydrocarbon, CO, and nitrogen oxide emissions were increased with the increase of CBD ratio. Biodiesel showed the maximum increase in specific fuel consumption by 10% and the thermal efficiency was decreased by 10.5% about pure diesel. Smoke emissions were decreased for CBD100 by 12% about gas oil. The maximum increases in NOx, CO, HC emissions, and exhaust gas temperature for CBD 100 were 22, 34, 48, and 11%, respectively related to diesel oil. The maximum reductions in cylinder pressure and net heat release rate were 5 and 13% for CBD100 about gas oil, respectively. Biodiesel percentage of 10% showed near values of performance parameters and emissions to gas oil, so, it is recommended as the optimum percentage.